Students Study Tour for Writing Media: Does It Work? - Suratni Suratni; Refi Yuliana (CV. Rayyan Dwi Bharata, 2023)
The study tour to Yogyakarta is an annual activity carried out by several Depok, West Java schools. This activity aims for cultural tourism, nature tourism, as well as refreshments for students. The article focuses on how the use of study tour activities as a medium for writing book manuscripts for junior high school students is correlated with the school's literacy program. The method used is the participatory method, involving 74 students of SMP Negeri 10 Depok. The steps taken were (1) discussions with school partners, (2) nonfiction writing workshops, (3) writing assistance, and (4) an editorial process. School partners support this activity by assigning four teachers as facilitators or accompanying teachers. The nonfiction writing workshop is in the form of a webinar and was held before the study tour. Writing assistance is provided by the team to students both individually and in groups. The finished manuscripts written by students then enter the editorial process, including the editing and graphic design processes. The book Healing and Exploring Yogyakarta is the outcome of this activity and will be published by Shinna Media Publishing.